Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1186/1741-7015-7-33
|View full text |Cite
|
Sign up to set email alerts
|

Treating 4,000 diabetic patients in Cambodia, a high-prevalence but resource-limited setting: a 5-year study

Abstract: BackgroundDespite the worldwide increasing burden of diabetes, there has been no corresponding scale-up of treatment in developing countries and limited evidence of program effectiveness. In 2002, in collaboration with the Ministry of Health of Cambodia, Médecins Sans Frontières initiated an outpatient program of subsidized diabetic care in two hospital-based chronic disease clinics in rural settings. We aimed to describe the outcomes of newly and previously diagnosed diabetic patients enrolled from 2002 to 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…The real world practice might not have given strong consideration to interventions that would improve patient empowerment and lifestyle modifications, with greater support in patient self management resulting in a suboptimal proportion of diabetic patients reaching their desirable targets. Diabetic programmes in Cambodia consisting of outpatient clinics with GPs, nurses, drug educators, and adherence counsellors showed significant clinical improvements in glycaemic control, but only a relatively low proportion of patients reached their treatment targets 37. A study on African-American adults has shown the importance of incorporating the empowerment principles in supporting DM patient self management in ‘real world’ settings 38.…”
Section: Discussionmentioning
confidence: 99%
“…The real world practice might not have given strong consideration to interventions that would improve patient empowerment and lifestyle modifications, with greater support in patient self management resulting in a suboptimal proportion of diabetic patients reaching their desirable targets. Diabetic programmes in Cambodia consisting of outpatient clinics with GPs, nurses, drug educators, and adherence counsellors showed significant clinical improvements in glycaemic control, but only a relatively low proportion of patients reached their treatment targets 37. A study on African-American adults has shown the importance of incorporating the empowerment principles in supporting DM patient self management in ‘real world’ settings 38.…”
Section: Discussionmentioning
confidence: 99%
“…While the number of persons with diabetes in need for care increases, inadequate supply of diagnostics and medicines, lack of staff, poor quality of care and high out-of-pocket payment hamper the delivery of continuous care for people with lifelong conditions [2][3][4]. Improvements in access mostly relate to decentralisation of care to the primary care level [5][6][7][8] or in special outpatient clinics [9]. Task-shifting to Community Health Workers (CHWs) or expert patients is less frequent [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Two prospective studies conducted in hospital‐based chronic disease clinics in rural Cambodia showed encouraging results in blood pressure and glycaemic control, but high losses to follow‐up remained a challenge (Raguenaud et al . ; Isaakidis et al . ).…”
Section: Introductionmentioning
confidence: 99%